Electric-field control of nonlinear THz spintronic emitters - Agarwal, Piyush (2023)
Energy-efficient spintronic technology holds tremendous potential for the design of next-generation processors to operate at terahertz frequencies. Femtosecond photoexcitation of spintronic materials generates sub-picosecond spin currents and emission of terahertz radiation with broad bandwidth. However, terahertz spintronic emitters lack an active material platform for electric-field control. Here, we demonstrate a nonlinear electric-field control of terahertz spin current-based emitters using a single crystal piezoelectric Pb(Mg1/3Nb2/3)O3-PbTiO3 (PMN-PT) that endows artificial magnetoelectric coupling onto a spintronic terahertz emitter and provides 270% modulation of the terahertz field at remnant magnetization. The nonlinear electric-field control of the spins occurs due to the strain-induced change in magnetic energy of the ferromagnet thin-film. Results also reveal a robust and repeatable switching of the phase of the terahertz spin current. Electric-field control of terahertz spintronic emitters with multiferroics and strain engineering offers opportunities for the on-chip realization of tunable energy-efficient spintronic-photonic integrated platforms.